Usefulness of the Continuous Glucose Monitoring (Freestyle Device) to Assess Glycemic Control of Diabetic Patients With and Without COVID 19 in a Hospital of Bogotá Colombia - Medina, Adriana (J Endocr Soc, 2021)
In the context of the COVID19 pandemic, diabetes mellitus constitutes a main risk factor that increases overall mortality (1). The continuous glucose monitoring system (CGM) is an alternative that allows strict glucose monitoring and reduces the contact of the healthcare providers with the patients in the pandemic era. We conducted a study using CGM in COVID vs non-COVID patients hospitalized at the San José Hospital in Bogotá Colombia. Methods: Single center, prospective study of glucose monitoring in patients with and without COVID19 using the Freestyle system. We included patients of 18 years and older, hospitalized at Hospital San José de Bogotá, with diagnosis of diabetes and treated with insulin. We used the T student distribution to analize the data. Primary outcomes were the usefulness of the device in inpatients, and the clinical outcomes according to glucometric measures in patients with and without COVID19 infection. Results: CGM devices were placed on 30 patients: 10 with, and 20 without COVID. The system was feasible with good nurse acceptance. The age of the patients was between 18 and 90 years. Of the COVID positive patients, 30% required ICU and 10% died, the mean HBA1C was 9.5% (CI 95% 7.5–10.09%) with a general variability of 35.6%, only 3 patients archieved goals of time in range. The general glycemic index was 7.04% (CI 0.66-0.100)Of the non COVID patients, 10% required ICU and 10% died, the average variability was 30.9% and hypoglycemic episodes predominated in 3 patients. The general glycemic index was 6.6% (CI 0.61–0.71)The patients who required ICU had an average HBA1C of 10.4%, 80% received corticosteroid management during the hospital stay. No patient had skin or soft tissue infection at the sensor insertion site. Conclusions: During the COVID-19 pandemic, CGM is a useful method for glucometric control that reduces the contact of healthcare providers and allows early interventions to improve metabolic control. Worse outcomes are seen in patients with higher variability and with COVID infection. References: 1. Apicella M. Campopiano MC. Mantuano M. Mazoni L. Coppelli A. Del Prato S. COVID-19 in people with diabetes: understanding the reasons for worse outcomes. Lancet Diabetes Endocrinol.2020: 8; 782–92.